Lipid Acquisition by Intracellular Chlamydiae - Elwell, Cherilyn A. (2012)
Chlamydia species are obligate intracellular pathogens that are important causes of human genital tract, ocular, and respiratory infections. The bacteria replicate within a specialized membrane-bound compartment termed the inclusion and require host-derived lipids for intracellular growth and development. Emerging evidence indicates that Chlamydia has evolved clever strategies to fulfill its lipid needs by interacting with multiple host cell compartments and redirecting trafficking pathways to its intracellular niche. In this review, we highlight recent findings that have significantly expanded our understanding of how Chlamydia exploit lipid trafficking pathways to ensure the survival of this important human pathogen.